Dioctophyme renale (Nematoda: Dioctophymatidae) in Leopardus geoffroyi (Carnivora: Felidae) in the Neotropical region - Trindade,Maira Aparecida Christello (2018)
Abstract Parasitic diseases affecting wild carnivores remain largely unknown or poorly described. Dioctophymosis is a parasitosis caused by the nematode Dioctophyme renale that is found worldwide. It affects domestic and wild animals and has been reported frequently in Brazil. This paper reports dioctophymosis in a wild felid for the first time.